Chaos making a new science - Gleick, James (London Abacus, a division of Little, Brown and Company (UK) Limited, 1993)
The author describes how scientists studying the growth of complexity in nature are discovering order and pattern in chaos. He explains concepts such as nonlinearity, the Butterfly Effect, universal constants, fractals, and strange attractors, and examines the work of scientists such as Mitchell J. Feigenbaum, Edward Lorenz, and Benoit Mandelbrot.
The butterfly effect -- Revolution -- Life's ups and downs -- A geometry of nature -- Strange attractors -- Universality -- The experimenter -- Images of chaos -- The dynamical systems collective -- Inner rhythms -- Chaos and beyond.
Includes bibliographical references (pages 318-340) and index.
Keywords: Chaotic behavior in systems